The AMPD1 C34T mutation is not associated with the status of Israeli athletes - Meckel, Y.; Nemet, D.; Alves, A. J.; Eliakim, A. (European Journal of Sport Science, 2012)
The adenosine monophosphate deaminase (AMPD1) gene seems to be an important regulator of skeletal muscle energy metabolism during exercise. A nonsense C34T mutation in the AMPD1 gene results in a premature stop codon, thus stopping protein synthesis. The aim of this study was to determine the AMPD1 C34T mutation frequency distribution among 155 Israeli athletes (endurance athletes, n=74; sprinters, n=81) and 142 healthy controls. Genotyping of the AMPD1 C34T (rs5810761) mutation was performed using polymerase chain reaction (PCR). Results showed that the genotype subtype did not differ by gender in the athletes (P=0.18) or the controls (P=0.79). The AMPD1 C34T genotype distribution was in line with Hardy-Weinberg equilibrium within all groups (P>0.05). The genotype distribution and allele frequencies were similar in the groups of endurance athletes, sprinters, and controls (P=0.455). Similarly, no significant differences were observed between the subgroups of elite endurance athletes and national endurance athletes (P=0.78), or between elite and national sprinters (P=0.46). In conclusion, the AMPD1 C34T mutation is not associated with endurance athletes` status, at least in the present group of Israeli athletes. This suggests that elite athletic status can be achieved despite a partial deficiency in AMPD1, as marked by the AMPD1 CT genotype.